A quantitative single-nanowire study on the plasmonic enhancement for the upconversion photoluminescence of rare-earth-doped nanoparticles. Issue 10 (4th April 2022) - Su, Xin; Chen, Li-Wei; Zhu, Zhejiaji; Li, Jiani; Zhang, Nan; Bu, Tong-An; Hao, Yu-Chen; Gao, Wen-Yan; Liu, Di; Wu, Si-Qian; Yu, Zi-Long; Huang, Hui-Zi; et al.
Abstract : The enhancement effects of the upconversion photoluminescence of rare-earth-doped nanoparticles by the localized surface plasmon resonance of a single Ag nanowire are quantified on a single-nanowire scale assisted by selective etching treatment. Abstract : Local surface plasmon resonance (LSPR) modulation represents a promising way for enhancing upconversion photoluminescence (UCPL). The study on the coupling mechanism of LSPR and UCPL is of great importance for both fundamental research and practical applications. However, general protocols based on the collective signals of mixed samples always suffered from the wide distributions of samples and inevitable interferences from the scattering and/or absorption of the surrounding samples, preventing the mechanism study with high accuracy and fidelity. Herein, we report a high-accuracy and quasi in situ study on the coupling of LSPR and UCPL in a single nanowire way. We chemically attached rare-earth (RE)-doped upconversion nanoparticles to Ag nanowires (UCNPs/AgNWs) and finely tuned their spectrum match, spacers, and surface coverages. We also developed a quasi in situ selective etching method to achieve LSPR–UCPL coupling on a single-nanowire scale with high accuracy. Our results proved that the LSPR enhancement of UCPL showed a strong dependence on the spectrum match and the distances between the LSPR and UCPL units. Compared with collecting average signals from the mixed samples, our single-nanowire method provides a superior approach to quantifying the LSPR–UCPL coupling with high accuracy and fidelity. These strategies may find more applications in the study of LSPR and/or UCPL materials, leading to a deeper understanding of the coupling mechanism of surface plasmon and photoluminescence processes.